Proflavine (PFH+): as a photosensitizer (PS) biocatalyst for the visible-light-induced synthesis of pyrano [2,3-d] pyrimidine scaffolds - Mohamadpour, Farzaneh; Amani, Ali Mohammad (Frontiers in Chemistry, 2024)
A sustainable methodology for the synthesis of pyrano [2,3-d] pyrimidine scaffolds have been developed, employing the Knoevenagel-Michael tandem cyclocondensation reaction of barbituric acid/1,3-dimethylbarbituric acid, malononitrile, and aryl aldehydes. This study elucidates the advancement of a sustainable and environmentally conscious approach to synthesizing this category of chemical compounds. In the present investigation, a novel photosensitizer comprising proflavine (PFH+) bio-photocatalyst was employed in an aqueous medium, subjected to air atmosphere at room temperature, and stimulated by a blue-light-emitting diode (LED) to harness renewable energy. The fundamental objective of this initiative is to utilize a photosensitizer (PS) biocatalyst that has been recently developed, can be conveniently acquired, and is priced affordably. The proflavine (PFH+) photocatalyst, demonstrates the ability to initiate photoinduced-electron transfer (PET) through exposure to visible light. This property endows the photocatalyst with a practical and efficient method of achieving high effectiveness, energy efficiency, and environmentally friendly outcomes. The current research endeavor has the objective of examining the turnover number (TON) and turnover frequency (TOF) pertaining to pyrano [2,3-d] pyrimidine scaffolds. Moreover, it has been validated that cyclization at the gram-scale is a feasible approach that can be employed in various industrial settings.